Renal effects and vascular reactivity induced by Tityus serrulatus venom - Alves, R. D.; do Nascimento, NRF; Barbosa, PSF; Kerntopf, M. R.; Lessa, LMA; de Sousa, C. M.; Martins, R. D.; Sousa, D. F.; de Queiroz, MGR; Toyama, M. H.; Fonteles, M. C.; Martins, AMC; et al. (Elsevier B.V., 2005)
Tityus serrulatus, popularly known as yellow scorpion, is one of the most studied scorpion species in South America and its venom has supplied some highly active molecules. The effects of T. serrulatus venom upon the renal physiology in human showed increased renal parameters, urea and creatinine. However, in perfused rat kidney the effects were not tested until now. Isolated kidneys from Wistar rats, weighing 240-280 g, were perfused with Krebs-Henseleit solution containing 6% (g weight) of previously dialysed bovine serum albumin. The effects of T. serrulatus venom were studied on the perfusion pressure (PP), renal vascular resistance (RVR), urinary flow (UF), glomerular filtration rate (GFR), sodium tubular transport (%TNa+), potassium tubular transport (%TK+) and chloride tubular transport (%TCl-). Tityus serrulatus venom (TsV; 10 mu g/mL) was added to the system 30 min after the beginning of each experiment (n = 6). This 30 min period was used as an internal control. The mesenteric bed was perfused with Krebs solution kept warm at 37 T by a constant flow (4 mL/min), while the variable perfusion pressure was measured by means of a pressure transducer. The direct vascular effects of TsV (10 mu g/mL/min; n=6), infused at a constant rate (0.1 mL/min), were examined and compared to the infusion of the vehicle alone at the same rate. TsV increased PP (PP30'= 127.8 +/- 0.69 vs PP60' = 154.2 +/- 14 mmHg*, *p < 0.05) and RVR (RVR30' = 6.29 +/- 0.25 vs RVR60' = 8.03 +/- 0.82 mmHg/mL g(-1) min(-1)*, *p < 0.05), decreased GFR (GFR(30') =0.58 +/- 0.02 vs GFR(60') = 0.46 +/- 0.01 mL g(-1) min(-1)*, *p < 0.05) and UF (UF30' = 0.135 +/- 0.001 vs UF60' = 0.114 +/- 0.003 mL g(-1)min(-1)*, *p < 0.05). Tubular transport was not affected during the whole experimental period (120 min). on the other hand, the infusion of TsV (10 mu g/mL/min) increased the basal perfusion pressure of isolated arteriolar mesenteric bed (basal pressure: 74.17 +/- 3.42 vs TsV 151.8 +/- 17.82 mmHg*, *p < 0.05). TsV affects renal haemodynamics probably by a direct vasoconstrictor action leading to decreased renal flow. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Tityus serrulatus; perfused kidney; mesenteric blood vessels